Systematic significance of foliar epidermis and tendril morphology in three West African genera of Cucurbitaceae: Momordica L., Luffa Mill. and Trichosanthes L. Issue 1 (2nd January 2016) - Kadiri, Akeem Babalola; Olowokudejo, James Dele
Abstract : Momordica, Luffa and Trichosanthes are important cucurbitaceous plants whose foliar epidermal characters are sparsely documented. A combined investigation of leaf epidermis and tendrils of the species was carried out with the aid of light and scanning electron microscopy, and visual assessment. All Momordica species have hypostomatic leaves except M. balsamina whose leaves are amphistomatic. This adds to our knowledge of range of stomatal distribution in Momordica which hitherto, is reported hypostomatic. It also raises doubt about the naturalness of Sect. Momordica . Only M. multiflora is glabrous and M. angustisepala alone is pubescent on the epidermal surfaces. Epidermis of Luffa is amphistomatic and non-cystolithic whereas, it is hypostomatic and cystolithic in Trichosanthes . Tendrils branches arise from the base in Luffa (3–4 in number) and Trichosanthes (2–3 in number) whereas in Momordica they may not branch or are bifurcated, with one being vestigial. These comparative data support classifying the three genera in separate tribes. In particular, characters of the leaf epidermis will assist in identifying the species even when the leaf samples are fragmentary, or when there is a mix-up, the usual state of herbal materials in the African markets.